The jurisdiction of shari'ah courts in the application of Islamic penal law : a study in Katsina State of Nigeria - Abba, Falalu (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2015)
This dissertation examines the jurisdiction of Shari'ah Courts of Katsina State of Nigeria as regards to the application of Islamic Penal law alongside with the jurisdiction of the civil courts in the State. Technically, the jurisdiction of a court is the actual authority that is vested in a Court for the exercising of judicial power in a particular case. The authority is customarily conferred on a court by the Statute that establishes such Court. The Shari'a Courts in Katsina State of Nigeria are established pursuant to the law by the Katsina State Legislature within the power that is conferred on it by the Constitution of the Federal Republic of Nigeria. The research also analyses the overlapping of jurisdiction between the Shari'a Courts and other civil Courts, which further resulted in uncertainty as to which of the Courts' jurisdiction that Muslims of Katsina State are really subjected to. The methodology used in this research is a doctrinal legal analysis in which materials gathered from the library and the registry of some Courts in Katsina State is analysed. The research finds that, the penal jurisdiction conferred on the Shari'a Courts in Katsina State is more in the legislative pronouncement than actual exercise of the jurisdiction by the Courts. In consequence, the research finds that other provisions in the Nigerian Constitution and some legislation by the Katsina State legislature in respect of the jurisdiction of civil Courts are overlapping with the penal jurisdiction of Shari'a Courts in the State. It also finds that Muslims in Katsina State are denied the certainty of jurisdiction and laws to be applied on them in criminal proceedings despite the glaring provisions that render all Muslims subject of the jurisdiction of the Shari'a Courts and in accordance with the Shari'a Penal Code of Katsina State. The research then recommends for the amendment and or repeal of some provisions to ensure harmonious coexistence between the Shari'a Courts and civil Courts for the smooth dispensation of criminal justice in Katsina State.